La Sostenibilidad de la Política Fiscal: El Caso de Ecuador - Maldonado , Diego (2007)
Through this paper it is being developed a model which evaluates the sustainability of the fiscal policy that permits public goals been reached in the medium term. With that purpose in mind, it is analyzed the ability of the government to honor its debt as well as 1ts capacity to increase its leverage, as required. Using Monte Carlo simulations and optimization techniques to stress out fiscal financial accounts, control variables have been found and subsequently 1t has been possible to identify the impact of these key variables on the defined fiscal sustainability objective function. Along the paper 1t is concluded that current fiscal policies applied on Ecuador do not satisfy the condition of sustainability and therefore new policies that fulf11l this requirement have been proposed.